Acetaldehyde binding energies: a coupled experimental and theoretical study. Issue 2 (29th August 2022) - Ferrero, S; Grieco, F; Ibrahim Mohamed, A-S; Dulieu, F; Rimola, A; Ceccarelli, C; Nervi, C; Minissale, M; Ugliengo, P
ABSTRACT: Acetaldehyde is one of the most common and abundant gaseous interstellar complex organic molecules found in cold and hot regions of the molecular interstellar medium. Its presence in the gas-phase depends on the chemical formation and destruction routes, and its binding energy (BE) governs whether acetaldehyde remains frozen on to the interstellar dust grains or not. In this work, we report a combined study of the acetaldehyde BE obtained via laboratory temperature programmed desorption (TPD) experiments and theoretical quantum chemical computations. BEs have been measured and computed as a pure acetaldehyde ice and mixed with both polycrystalline and amorphous water ice. Both calculations and experiments found a BE distribution on amorphous solid water that covers the 4000–6000 K range when a pre-exponential factor of 1.1× 10^18 s^-1 is used for the interpretation of the experiments. We discuss in detail the importance of using a consistent couple of BE and pre-exponential factor values when comparing experiments and computations, as well as when introducing them in astrochemical models. Based on the comparison of the acetaldehyde BEs measured and computed in the present work with those of other species, we predict that acetaldehyde is less volatile than formaldehyde, but much more than water, methanol, ethanol, and formamide. We discuss the astrochemical implications of our findings and how recent astronomical high spatial resolution observations show a chemical differentiation involving acetaldehyde, which can easily explained due to the different BEs of the observed molecules.